2023
DOI: 10.1186/s13099-023-00533-4
|View full text |Cite
|
Sign up to set email alerts
|

CMTM3 protects the gastric epithelial cells from apoptosis and promotes IL-8 by stabilizing NEMO during Helicobacter pylori infection

Abstract: Background CKLF-like MARVEL transmembrane domain containing 3 (CMTM3) plays an important role in cancer development. Although Helicobacter pylori (H. pylori) infection is a main cause of gastric cancer, the function of CMTM3 during H. pylori infection remains unclear. CMTM3 expression levels in tissues from H. pylori-infected patients and cells co-cultured with H. pylori were analyzed. qRT-PCR and ELISA were used to investigate the effects of CMTM3 on interleukin 8 (IL-8) expression. Annexin V/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Notably, we found that pretreatment, post-treatment, and cocultivation with ILA effectively mitigate the number of late apoptotic cells triggered by H. pylori (Figure D), thereby potentially contributing to the integrity of the gastric mucosa …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Notably, we found that pretreatment, post-treatment, and cocultivation with ILA effectively mitigate the number of late apoptotic cells triggered by H. pylori (Figure D), thereby potentially contributing to the integrity of the gastric mucosa …”
Section: Resultsmentioning
confidence: 93%
“…Due to its induction of a reduction in gastric acid secretion and an increase in cell monolayer disintegration, apoptosis is advantageous for the establishment of H. pylori colonization and the disruption of local homeostasis. 31 Therefore, ILA also plays a protective role in preserving the integrity of gastric mucosal epithelial cells, thereby aiding resistance against invasion by H. pylori. The progression of H. pylori-induced gastric disease is typically accompanied by oxidative stress and inflammatory damage to the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The H. pylori -cell co-culture experiment was carried out as described previously. 61 , 62 Briefly, H. pylori collected from the solid medium was washed and resuspended in phosphate buffered saline (PBS). The quantity of H. pylori was measured at 600 nm absorbance using a spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%